2014
DOI: 10.1039/c4fd00106k
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the simple proportionality between molecular conductances and charge transfer rates

Abstract: A theoretical framework is presented to describe and to understand the observed relationship between molecular conductances and charge transfer rates across molecular bridges as a function of length, structure, and charge transfer mechanism. The approach uses a reduced density matrix formulation with a phenomenological treatment of system-bath couplings to describe charge transfer kinetics and a Green's function based Landauer-Buttiker method to describe steady-state currents. Application of the framework is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 50 publications
4
74
0
Order By: Relevance
“…We find that the conductance features of the TP1 breadboard, and relative conductance trends for various circuits are insensitive to whether the transport takes place in the hole dominated or electron dominated regime (see Section S.9 of ESI†). For the large barriers (>1 eV) and small molecular bridge lengths (<20 Å) for the TP1 system studied here, charge transport takes place via tunneling 49 and the conductance is dominated by the contribution at the Fermi energy: 42 …”
Section: Methodsmentioning
confidence: 99%
“…We find that the conductance features of the TP1 breadboard, and relative conductance trends for various circuits are insensitive to whether the transport takes place in the hole dominated or electron dominated regime (see Section S.9 of ESI†). For the large barriers (>1 eV) and small molecular bridge lengths (<20 Å) for the TP1 system studied here, charge transport takes place via tunneling 49 and the conductance is dominated by the contribution at the Fermi energy: 42 …”
Section: Methodsmentioning
confidence: 99%
“…Summary of the single molecule conductance measurements for the nucleic acid duplexes.The Büttiker-Landauer probe approach was used to calculate the molecular conductances [50][51][52]. Büttiker virtual electrodes were introduced to simulate the dephasing induced by the interaction of the molecule with the environment.…”
mentioning
confidence: 99%
“…Previous studies with the LBP technique had demonstrated its utility as a means to phenomenologically describe low-bias incoherent effects in mesoscopic conductors 25,[28][29][30][31][32][33][34][35][36] and molecular junctions 27,[37][38][39][40][41][42] These simulations indicate that the LBP technique can reproduce several key features in molecular electronic conduction: A "Kramers-like" turnover of conductance as a function of the so-called dephasing strength, an onset of a thermally activated conductance at high temperature, and a transition from tunneling to ohmic conduction when increasing the molecular size 27 . It was also shown in Ref.…”
Section: Introductionmentioning
confidence: 99%